PENDIDIKAN KARAKTER PADA SEKOLAH DASAR DI INDONESIA DAN AMERIKA - Arifin; Ndraha, Lies Dian Marsya; Djara , Jean Imaniar; Nitiasih, Putu Kerti; Riastini, Putu Nanci (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2024)
Teaching good values in various aspects of life is the main thing that we must live by, as Ki Hadjar Dewantara and Emanuel Khant emphasize goodness in all aspects of life. This means that educated teenagers are not under the doctrinaire rules of education solely through the amount of cognitive value they obtain as a result of studying at school, but more than that, the realization of the value obtained is the main thing. This research is library research by looking for references from various national and international articles. The data obtained was analyzed using content analysis. Based on the results of the research and discussion, it can be concluded that character education in Indonesia is influenced by the thoughts of Ki Hadjar Dewantara, while America is influenced by the thoughts of Imanuel Khant. Character education in basic education in Indonesia and America has a different development focus. Indonesia is currently focusing on the characters packaged in the Pancasila Student Profile. Meanwhile in America the focus is on the character of trust, respect, responsibility, justice, caring, citizenship, honesty, courage, perseverance and integrity which are packaged in educational institutions through honest schools